A photochemical and theoretical study of the triplet reactivity of furano- and pyrano-1, 4-naphthoquionones towards tyrosine and tryptophan derivatives. Issue 24 (30th April 2019) - Teixeira, Rodolfo I.; Goulart, Juliana S.; Corrêa, Rodrigo J.; Garden, Simon J.; Ferreira, Sabrina B.; Netto-Ferreira, José Carlos; Ferreira, Vitor F.; Miro, Paula; Marin, M. Luisa; Miranda, Miguel A.; de Lucas, Nanci C.
Abstract : Biologically active naphthoquinones undergo photochemical induced hydrogen abstraction from biologically relevant substrates via a PCET mechanism. Abstract : The photochemical reactivity of the triplet state of pyrano- and furano-1, 4-naphthoquinone derivatives (1 and2 ) has been examined employing nanosecond laser flash photolysis. The quinone triplets were efficiently quenched byl -tryptophan methyl ester hydrochloride, l -tyrosine methyl ester hydrochloride, N -acetyl-l -tryptophan methyl ester and N -acetyl-l -tyrosine methyl ester, substituted phenols and indole ( k q ∼10 9 L mol −1 s −1 ). For all these quenchers new transients were formed in the quenching process. These were assigned to the corresponding radical pairs that resulted from a coupled electron/proton transfer from the phenols, indole, amino acids, or their esters, to the excited state of the quinone. The proton coupled electron transfer (PCET) mechanism is supported by experimental rate constants, isotopic effects and theoretical calculations. The calculations revealed differences between the hydrogen abstraction reactions of phenol and indole substrates. For the latter, the calculations indicate that electron transfer and proton transfer occur as discrete steps.